Training Needs of Algerian Faculty Members in LMD System - Fatiha Benzeroual; Sabah Nasraoui (المجلة العربية لضمان جودة التعليم الجامعي, 2016)
Abstract:                                                                           The success of the change, that Algerian university has adopted through the application of LMD system, depends   the preparation of the university with all its components to this change.